PEMANTAUAN PROSES EKSTRAKSI Curcuma xanthorrhiza Roxb. DENGAN METODE REFRAKTOMETRI DAN GRAVIMETRI - Charlyna Veronika Puspitasari Pattymahu; Idha Kusumawati; Dewi Isadiartuti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Rapid in-process control (IPC) is essential in the extraction of Curcuma xanthorrhiza Roxb. rhizomes to ensure quality consistency. Refractometry based on Total Soluble Solids (TSS) offers an efficient IPC alternative; however, its quantitative validity relative to gravimetric yield in hydroalcoholic matrices requires systematic verification. This study aimed to evaluate the correlation between TSS profiles (°Brix) and total solids yield during the stepwise ultrasound-assisted extraction (UAE) of C. xanthorrhiza rhizomes using 70% ethanol. Extraction was performed using a sonicator bath (40 kHz, 120 W) in a stepwise manner (E1-E12) with sampling intervals every 30 minutes up to 360 minutes. Physicochemical parameters were monitored via TSS values (°Brix) and compared with gravimetric total solids determination. The relationship between variables was analyzed using Spearman correlation and linear regression. The analysis demonstrated a strong Spearman correlation between °Brix values and yield (ρ = 0.984; p < 0.001). The linear regression model showed high predictive accuracy with an R² of 0.986, and low error rates (MAE = 0.09% and RMSE = 0.14%). A stable plateau phase was reached at stages E9-E12, achieving a maximum yield of 8.31% at a TSS value of 9.00 °Brix. The refractometric method is a valid, rapid, and reliable IPC tool for monitoring the ultrasonic extraction of C. xanthorrhiza, providing real-time yield estimation comparable to the conventional gravimetric method.